ENSIKLOPEDIA ALAT TRANSPORTASI JAKARTA BERBASIS AUGMENTED REALITY - Dharmayanti Dharmayanti; Dimas Dwi Permana; Elvina Elvina (Institut Transportasi dan Logistik Trisakti, 2016)
This writing explains about encyclopedia book of Jakarta’s Means of transportation using augmented reality technique. This encyclopedia book consists of 7 (seven) sheets which each one discusses about the Jakarta’s means of transportation with a marker named QR-code. Each marker on each sheet shows a means of transportation model in 3D (dimension) along with the animation. This book is made by using library AR Toolkit software. Blender 2.64 application is used to make the 3D Jakarta means of transportation, meanwhile Adobe Photoshop CS4 is used to make the marker. The output of this application is 3D vehicle models with animation that can be seen when webcam is pointed to the marker. This application is made as a new learning and introduction media for the society especially kids to know more about means of transportation operated in Jakarta.